Editorial - Jörg Tremmel; Edward Page; Konrad Ott (Intergenerational Justice Review)
Next to the swelling book shelves in the natural sciences, there is a growing library on the ethics of climate policy. This is of small surprise as anthropocentic climate change is one of the greatest problems facing mankind. The impacts of climate change pose a clear threat to the rights and freedoms of many existing and future persons; and they will exacerbate inequalities between rich and poor countries. Dangerous climate change was usefully defined by the UN Framework Convention on Climate Change as a state of affairs where concentrations of CO2-equivalent (CO2e) in the atmosphere trigger climatic impacts sufficiently grave to threaten global food production, prevent sustainable economic development, and prevent ecosystems from adapting naturally. There are essentially four distinct ethical concepts involved: